Unemployment in ASEAN countries: panel data analysis - Muhamad Mustaqim Azmi, Hamdan Kumaran (2021)
Lately, the issue of unemployment is much debated and received attention in most countries including countries in ASEAN. It is one of the key factors that is considered critical for the growth and economic recession of a country. Most earlier researchers conducted a large number of studies on unemployment concerns, but they did not place a high priority on conceptual analysis and empirical evidence. They only focus on economic elements such as inflation, gross domestic product (GDP), and capital formation as an independent variable. Therefore, this study combines economic elements such as inflation, gross domestic product (GDP), and capital formation and individual factors namely employability skills and English proficiency towards unemployment especially during the Covid-19 Pandemic crisis among ASEAN countries (Brunei Darussalam, Cambodia, Indonesia, Laos, Malaysia, Myanmar, Philippines, Singapore, Thailand and Vietnam. This study uses secondary data or panel data from three major platforms namely the World Bank, World Economic Indicators and Macro Trends covering 10 ASEAN member states from the period of 2000 to 2019. This study uses five major analysis techniques namely Descriptive Analysis, Correlation Analysis, Ordinary Least Squares (OLS) Panel Regression, Autoregressive Distributed Lag Model (ARDL), and Panel Cointegration. There are two theoretical foundations for this study which is the theory of Phillips curve and the Okun’s law. Secondary data is used to meet the objectives of the study. According to the findings, inflation and GDP have negative correlations with unemployment; as unemployment rises, inflation and GDP fall, and vice versa. In addition, GDP and inflation are found to have significant value below 0.05 or 5%. As a consequence, the researcher is sure that the findings are consistent with all past research studies. This research study will give ideas and knowledge, particularly to ASEAN member nations, on current challenges, and urgent action in terms of fiscal and monetary policy may be made to improve the ASEAN member countries' economies.